Direct Sexist in Pitch Perfect Series Movies - Rudha Widagsa; Aulia Nisa’ Khusnia (Journal on Education, 2022)
The term "sexist language" refers to any form of speech that features or gives preference to one gender over another. As a form of discrimination based on a person's gender, sexism is unacceptable. The merits and flaws of society are reflected in this widely held belief. One of the most pervasive and unchangeable social norms is sexism. This article aims at finding the direct sexism found in the Pitch Perfect Series Movie. It belongs to qualitative research. The data for this study come in the form of individual words, phrases, and clauses within larger portions of text like sentences and paragraphs. Collecting data entails the following procedures: (1) downloading the film; (2) watching the film; (3) making notes on the film's use of language and setting; and (4) identifying examples of indirect sexism using the categories provided. There are data showing direct sexism. Those belong to humor, presupposition, conflicting messages, and endocentric messages. Words, phrases, and clauses within sentences and paragraphs represent the majority of this study's data. It's a joke, but shame, disappointment, prejudice, a clash between feminism and gender, and the male perspective all contribute to the perpetuation of sexism